(3fRgI GdXQaGA hJMaI GdNdaGAs - (3YHGS Hf Ydj Hf OGhO Hf GdeXaQ jhSa GdQShdj GdZSGfj, Gdedc GdCaVd , J (B778 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdbOQI hGdLdGd CeG HYO agPG eNJUQ jTJed Ydi QShe GdNdaG hCOGH NOeJge GdHGH GdChd ai BOGH NGUI Gdedhc s
(3BNQgG (B:s
(3bGd Gddg JYGdi bd gd jSJhi GdPjf jYdehf hGdPjf dG jYdehf EfeG jJPcQ ChdhG GdCdHGH hgPG BNQ eG GYJfjfG Hg ef LeY gPG GdeNJUQ Ydi MSH GdEecGf hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B262 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B61s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI MeO Hf YHO GdQMef GdYHjcGf GdNGUI HGdQjGV(B(953 / 223) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdJGQjNs